(untitled) (Research, Society and Development, 2021)
Chemical dependence on alcohol presents factors limiting treatment such as the occurrence of relapses, lack of therapeutic adherence, neurological disorders associated with or resulting from alcohol and synergistic, toxic or zero effects of alcohol. The present study aimed to identify the potential interactions between drugs and drug-alcohol in patients with treatment of chemical dependence on alcohol treated by a Psychosocial Care Center Alcohol and Drugs. Thus, a cross-sectional, descriptive observational study was carried out, developed during experiences experienced in the Health Work Education Program, interprofessionality theme. Data from 31 patients were evaluated from the analysis of medical records, as well as the evaluation of the book of records for dispensing psychotropic drugs. It was found that the patients seen in the unit were mostly male and aged between 19 and 59 years, 48.4% were smokers and 58.0% used illicit drugs. We identified 41 potential drug interactions (IM), as well as the occurrence of interactions between alcohol and prescribed medications. The evaluation of prescriptions, as well as the profile of these patients, demonstrated the importance of performing a pharmacotherapeutic follow-up of alcoholic patients, who are subject to numerous reactions resulting from MI and drug interactions with alcohol, avoiding situations of therapeutic failure, besides minimizing adverse events that may occur.